SOSIALISASI LITERASI DIGITAL PADA PELAKU UMKM DI PULAU KODINGARENG MENUJU â€œUMKM NAIK KELAS, UMKM GO DIGITALâ€ - Sri Wahyuningsih Piu; Muhammad Rizal; Arham Arifin; Andi Asvin Mahersatillah Suradi; Muhammad Furqan Rasyid; Imran Djafar; Asmah Akhriana; Sitti Aisa; Santi Santi; Suci Ramadhani Arifin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
Kodingareng Island is a small island located in the Spermonde Archipelago, South Sulawesi, Indonesia. Kodingareng Island does not have a large population or large development so that the number of MSME actors on this island may be limited. Digital literacy is becoming increasingly important for MSMEs, including on Kodingareng Island. To overcome the low level of digital literacy for MSMEs on Kodingareng Island, a team of Lecturers from Dipa Makassar University carried out community service activities in the form of socialization of digital literacy using a social campaign and media campaign approach to increase awareness and understanding of digital literacy issues. The purpose of this activity is to help MSME players recognize and overcome the challenges and risks associated with the use of digital technology. With effective dissemination of digital literacy, it is hoped that MSME actors can make the most of digital technology, while protecting themselves and contributing positively in the ever-evolving digital world.